Letter - Chamberlain, Neville, 1869-1940
012a-0136-001 Prime Minister 10, Downing Street, Whitehall, 1st February, 1938. I received this morning your letter about the bombing of towns in Spain, but I now learn that a Resolution is to be moved in the House of Commons by Mr. Morgan Jones, M.P., on the subject of the bombing of open towns. It will be necessary for the views of the Government to be fully stated during the debate and I hope, therefore, that you will be willing to await this statement and allow me to leave your letter unanswered. Yours sincerely N. [Neville] Chamberlain Sir Walter Citrine, K.B.E. 292/946/12a/136